Efficacy of amifostine in protection against doxorubicin-induced acute cardiotoxic effects in rats - Dragojević-Simić Viktorija; Dobrić Silva; Jaćević Vesna; Bokonjić Dubravko; Milosavljević Ivica; Kovačević Aleksandra; Mikić Dragan (Vojnosanitetski Pregled, 2013)
Background/Aim. Amifostine (AMI) is a broad-spectrum cytoprotector which protects against variety of radio- and chemotherapy-related toxicities without decreasing their antitumor action. The aim of the study was to investigate the potential protective effects of AMI against acute cardiotoxic effects of doxorubicin (DOX) in male Wistar rats. Methods. AMI (300 mg/kg ip) was given 30 min before DOX (6 mg/kg and 10mg/kg b.w., iv). The evaluation of DOXinduced cardiotoxic effects, as well as cardioprotective efficacy of AMI was performed 48 h after their administration by determining serum activities of enzymes known to be markers of cardiac damage (creatine kinase - CK, aspartate aminotransferase - AST, lactate dehydrogenase - LDH, and its isoenzyme α-hydroxybutirate dehydrogenase - α- HBDH), as well as the histopathological and ultrastructural analysis of the heart tissue. Results. AMI successfully prevented a significant increase in serum activity of CK, AST, LDH and α-HBDH in animals treated with DOX in the dose of 6 mg/kg (121.14 ± 18.37 vs 167.70 ± 44.24; 771.42 ± 161.99 vs 1057.00 ± 300.00; 3230.00 ± 1031.73 vs 4243.10 ± 904.06; 202.57 ± 42.46 vs 294.90 ± 80.20 UI/l, respectively), and ameliorated DOX-induced structural damage of the rat myocardium. Pretreatment with AMI in rats given 10 mg/kg DOX reduced the cardiac damage score (CDS) from 2.62 ± 0.51 to 1.62 ± 0.51, i.e. to the CDS value obtained with the lower dose of DOX (6 mg/kg). The ultrastructural analysis of the rat myocardium showed that AMI successfully protected the sarcolemma of cardiomyocytes and reduced mitochondria damage induced by DOX given in the dose of 6 mg/kg. Besides, capillaries were less morphologically changed and apoptosis of endothelial cells was extremely rare in AMI-protected animals. AMI itself did not cause any prominent changes in the examined parameters in comparison with the control rats. Conclusion. AMI provided a significant protection against DOX-induced acute cardiotoxic effects in rats. This finding implies its potential to be a successful cardioprotector in patients treated with DOX due to malignant diseases.